2021
DOI: 10.3389/fpsyg.2021.670800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Design Aesthetics on the Perceived Value of a Product

Abstract: Design aesthetics play a crucial role in product design. Stakeholders expect to develop highly valuable premium products by improving the design aesthetics of products. Nevertheless, the question of how to evaluate the value of design aesthetics has not been fully addressed. In this study, the effects of design aesthetics on the evaluation of the value of a product were investigated through a strictly controlled experiment in which the neural responses of the participants were measured. Forty participants comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
0
11
0
2
Order By: Relevance
“…When product design draws the interests or emotions of consumers, they may not care too much about the price of the product (Norman, 2004). Additionally, some research has pointed out that there are enormous variations in consumers' purchase intentions for products with high design aesthetics and products with low design aesthetics (Shi et al, 2021). Therefore, design aesthetics has a positive influence on consumers' purchase intention (Hagtvedt and Patrick, 2014).…”
Section: Hypothesis Development Design Aesthetics and Purchase Intentionmentioning
confidence: 99%
“…When product design draws the interests or emotions of consumers, they may not care too much about the price of the product (Norman, 2004). Additionally, some research has pointed out that there are enormous variations in consumers' purchase intentions for products with high design aesthetics and products with low design aesthetics (Shi et al, 2021). Therefore, design aesthetics has a positive influence on consumers' purchase intention (Hagtvedt and Patrick, 2014).…”
Section: Hypothesis Development Design Aesthetics and Purchase Intentionmentioning
confidence: 99%
“…N100 is an ERP component that reflects detection of objects ( Lijffijt et al, 2009 ; Shi et al, 2021 ) and is related to attention allocation; it is usually elicited by artificial product such as symbols, phones, and cars ( Lu and Hou, 2020 ; Hou and Yang, 2021 ). We found that human faces significantly elicited N170, and that vehicle faces elicited both N100 and N170, suggesting that vehicle faces were first processed as normal objects and subsequently elicited N100.…”
Section: Discussionmentioning
confidence: 99%
“…The ERP components N100 and N170 indicate object and face recognition in the early stages of information processing. N100 is an early stage ERP component that can be elicited between 80 and 150 ms after stimulus onset, reflecting object detection and recognition ( Lijffijt et al, 2009 ; Shi et al, 2021 ). It further reflects attention resource allocation or vigilance when appearing in the frontal and occipital regions ( Lijffijt et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be said that traditional culture subtly affects the life of modern people, providing a steady stream of elements and inspiration for product design. In particular, future design needs to return to the perspective of humanities and esthetics, and technology cannot be used as a simple auxiliary tool to guide design ( Shi et al, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%